Volunteer-aholism: A comprehensive model of personality, burnout, and mental distress in a sample of healthcare first responders of the Italian Red Cross Auxiliary Corps - Livio TARCHI; Pietro CRESCENZO; Giovanni CASTELLINI; Valdo RICCA; Kristian TALAMONTI; Fabio RISPOLI; Sefa BULUT; Amelia RIZZO; Salvatore ZAFFINA; Gabriele GIORGI; Francesco CHIRICO (Journal of Health and Social Sciences)
Introduction: Whether burnout can be extended to explain occupational distress in unwaged personnel is an ongoing debate. Possible divergences could be observed for burnout among nontraditional working figures. Methods: A total of 823 first responders during the COVID-19 pandemic were surveyed among Red Cross volunteers enrolled in the Italian Auxiliary Corps to the Armed Forces. An online questionnaire was proposed as composed of the Generalized Anxiety Disorder Assessment, Patient Health Questionnaire, Single-item PTSD Screener, Maslach Burnout Inventory, and Big Five Inventory. A comprehensive model accounting for both personality and mental distress in influencing burnout dimensions was carried over through structural equation modeling. Results: Almost perfect goodness of fit was achieved for the model (TLI >0.99; CFI >0.99; RMSEA <0.03). Emotional stability was negatively associated with depression (beta=-0.21) and anxiety (beta=-0.25). Conscientiousness (beta=0.29) and emotional stability (beta=0.21) were positively associated with personal accomplishment. Depression, anxiety, and personal accomplishment were positively associated with emotional exhaustion and depersonalization (minimum beta=0.2, maximum beta=0.36, all p<0.001). Discussion: A theoretical framework was offered to interpret results, according to which the defining characteristic predisposing for burnout was not whether operators were waged or not, but rather their degree of involvement with the occupational demands.